Suvremeno djetinjstvo i institucijski kontekst - Šagud, Mirjana (2014)
Recently, the study of the child and childhood as a social and cultural phenomenon is accessed from a position of exceptional complexity and multidimensionality. Childhood, as opposed to thinking of the majority of adults, is not isolated, protected, well controlled and predictable way of conducting a child into the adult world. Childhood focuses more on the general perception of the child and suggests the existence of a special, separate and fundamentally different social group and social category. Status of the child designed by adults and its culturally and historically specific construct changes and varies from its definition of physical and/or sexual maturity, legal status or age affiliation. The concept of the child and childhood is focused on the individual, and that is usually defined from the position of adults. Two extreme views of children and childhood are related to the concept of designing, modeling, building and desirable socialization, or emphasizing the concept where a child is considered as the main agent of childhood. Institutional Preschool context with all its aspects (cultural, curricular, financial and social determinants) can encourage and strengthen, or weaken all those advantages and potentials that childhood brings. In this sense, childhood does not exist outside the social context and its reflexive representation evident in the dynamic relations and divergently structured educational conditions.
ENG